2020
DOI: 10.3390/app10186294
|View full text |Cite
|
Sign up to set email alerts
|

Rock Breaking Performance of TBM Disc Cutter Assisted by High-Pressure Water Jet

Abstract: A high-pressure water jet can break rock efficiently, which is of great potential to overcome the problems of a tunnel boring machine (TBM) in full-face hard rock tunnel digging, such as low digging efficiency and high disc cutter wear rate. Therefore, this paper presented a new tunneling method that is a TBM coupled with a high-pressure water jet. The rock failure mechanism under the coupled forces of a disc cutter and water jet was analyzed at first. Then, the finite element method (FEM) and smoothed particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…It can be found that when the disc cutter is in contact with the rock sample, a stress concentration zone with mainly compressive stress will be generated beneath the disc cutter, and the farther away from the disc cutter, the smaller the degree of stress concentration, and the stress transfer to the position of the precutting slit is blocked, which is caused by the decompression effect of the precutting slit (Tan et al, 2012). As can be seen from the figure, due to the effect of the precutting slit tip, the bottom of the precutting slit also distributes the relative stress concentration zone (Wang et al, 2020), and the stress concentration zone tends to develop along the bottom of the precutting slit from beneath the disc cutter. Therefore, it appears that the stress concentration degree beneath the disc cutter is high on the precutting slit side and low on the non-precutting slit side, which is most significant when the precutting slit depth H is 30 mm and 40 mm.…”
Section: Effect Of Precutting Slits Parameters On Force Chain Field D...mentioning
confidence: 99%
“…It can be found that when the disc cutter is in contact with the rock sample, a stress concentration zone with mainly compressive stress will be generated beneath the disc cutter, and the farther away from the disc cutter, the smaller the degree of stress concentration, and the stress transfer to the position of the precutting slit is blocked, which is caused by the decompression effect of the precutting slit (Tan et al, 2012). As can be seen from the figure, due to the effect of the precutting slit tip, the bottom of the precutting slit also distributes the relative stress concentration zone (Wang et al, 2020), and the stress concentration zone tends to develop along the bottom of the precutting slit from beneath the disc cutter. Therefore, it appears that the stress concentration degree beneath the disc cutter is high on the precutting slit side and low on the non-precutting slit side, which is most significant when the precutting slit depth H is 30 mm and 40 mm.…”
Section: Effect Of Precutting Slits Parameters On Force Chain Field D...mentioning
confidence: 99%
“…It is most often composed of calcite-CaCO 3 or dolomite-CaMg(CO 3 ) 2 , by recrystallization. The main properties of marble are: porosity (%), density (g/cm 3 ), compressive strength (MPa), flexural strength (MPa), Amsler abrasion wear (mm/1000 m), hardness (Mohs), Young's modulus (GPa), fracture toughness (MPa/m) [2,14] and largely depend on the area from which it comes.…”
Section: The Process Of Creating and Propagating Microcracks In Marblementioning
confidence: 99%
“…A recent research study [13] proposes an approach to the complex process of cutting hard rock, analyzing and evaluating the intensity of the disintegration of abrasive materials in the process of cutting AWJ, during the creation of the abrasive jet. Some current processing models on abrasive water jet machines used in the analysis of the behavior of various materials, including rock type are presented in the papers [14][15][16], but in the field of marble cutting by AWJ process research is limited.…”
Section: Introductionmentioning
confidence: 99%
“…For hard coal seams, there are currently some new coalcrushing technologies, which are classified according to their working principles and can be divided into jet crushing [7][8][9], jet-assisted mechanical crushing [10][11][12][13], special-shaped pick crushing [14,15], and laser crushing [16,17]. In recent years, these methods were carried out fruitfully by scholars.…”
Section: Introductionmentioning
confidence: 99%